Functional Morphology of the Crop and Proventriculus of Sitophilus zeamais (Coleoptera: Curculionidae) - De Sousa, Gessica; Scudeler, Elton Luiz [UNESP]; Abrahao, Josielle; Conte, Helio (Entomological Soc Amer, 2013)
Sitophilus zeamais Motschulsky, 1855 (Coleoptera: Curculionidae) is one of the most aggressive pests of stored grains, causing significant decrease in the nutritional quality of the grains and major losses in economic trade. The ability of this pest to damage grains and other products is directly related to the morphology of the alimentary canal. Considering the importance of the foregut in the digestion, this study aimed to describe the morphology of the crop and proventriculus in S. zeamais adults. The tissues were isolated, processed, and analyzed by using light microscopy, scanning electron microscopy, and transmission electron microscopy. The crop functioned as a storage organ, and its cells showed functional characteristics related to protein synthesis. High densities of prokaryotic microorganisms and spicules were found in the lumen. The proventriculus exhibited eight chitinous teeth, which were responsible for grinding and filtering food particles. This organ formed the stomodeal valve, which controlled the unidirectional flow of food through the alimentary canal. The alimentary canal is the primary surface of contact between the external environment and an insect's internal environment, and knowledge of its morphology is required to better understand the physiology of stored-grain insect pests.
Keywords: alimentary canal; chitinous teeth; foregut; stomodeal valve